2006
DOI: 10.1111/j.1600-6143.2005.01153.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrapyloric Injection of Botulinum Toxin A for the Treatment of Persistent Gastroparesis Following Successful Pancreas Transplantation

Abstract: Intrapyloric injection of botulinum toxin A (BoTx) successfully improved symptoms in idiopathic and diabetic gastroparesis (DGP) refractory to medical treatment. Therefore, we used it in three pancreas transplant patients done in our institution during the last 18 months. They had severe, persistent DGP despite successful pancreas transplantation. They received 100 units of BoTx during the first injection. The clinical effect became evident within 2 weeks after the treatment, and lasted for an average of 29 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Improved nausea, fullness, bloating, and eructation have been observed in patients with idiopathic gastroparesis as well as disease due to diabetes, Nissen fundoplication, esophagectomy, and pancreatic transplantation [7][8][9][10][11][12][13][14][15]20]. Additional benefits include weight gain and improved quality of life [10].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Improved nausea, fullness, bloating, and eructation have been observed in patients with idiopathic gastroparesis as well as disease due to diabetes, Nissen fundoplication, esophagectomy, and pancreatic transplantation [7][8][9][10][11][12][13][14][15]20]. Additional benefits include weight gain and improved quality of life [10].…”
Section: Discussionmentioning
confidence: 92%
“…On manometric and scintigraphic testing, intrapyloric botulinum toxin injection reduces pyloric motor activity and accelerates gastric emptying in many gastroparesis patients [6][7][8][9][10][11]. Uncontrolled case series report symptom reductions after pyloric botulinum toxin injection in patients with refractory gastroparesis [7][8][9][10][11][12][13][14][15]. However, two small controlled trials have observed no benefits from this therapy compared with placebo [16,17].…”
Section: Introductionmentioning
confidence: 88%
“…177 Uncontrolled studies of endoscopic injections of botulinum toxin reported symptomatic improvement, as well as acceleration of gastric emptying in diabetic, [178][179][180][181] idiopathic [180][181][182] and postsurgical [183][184][185][186] gastroparesis; how ever, these bene fits have not been confirmed in subsequent blinded sham-controlled trials. 187,188 Accordingly, this approach cannot currently be recommended for t reatment of diabetic gastroparesis.…”
Section: Botulinum Toxinmentioning
confidence: 94%
“…Among the 210 initially potentially relevant studies, 195 were animal studies, duplicates, abstracts, editorials, or reviews and letters to the editor. Finally, 15 trials were included [13,14,15,16,17,25,26,27,28,29,30,31,32,33,34], among these trials there were only 2 RCTs [32,33], and the remaining 13 trials were non-randomized. The basic characteristics of the included studies are summarized in table 1.…”
Section: Resultsmentioning
confidence: 99%